Linear 2.4 GHz Array Optimization Using Genetic Algorithm Technique - Ibrahim, Dlnya Aziz; Mahmood, Aras Saeed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Genetic algorithm (GA) is global numerical optimization approach is based on the genetic recombination and assessment in nature. This kind of optimization can be utilized to optimize the amplitude, phase levels and spacing distribution for the elements of an antenna array to achieve its best performance. In this study the genetic algorithm of the 4NEC2X software has been used to optimize the element spacing (𝑑 = 𝜆 4 ) of both a uniform and non-uniform (Binomial and Chebyshev) current excitation for 10-element, 2.4 GHz linear broadside dipole antenna arrays. As a consequence, for the above-mentioned array antennas the spacing optimization yielded a notable improve in their directivity and Gain (dBi), such that for the uniform current excitation the gain was reached to 14.8dBi and for both Binomial and Chebyshev non-uniform current excitation the gain increased to 12.57 dBi and 15.04 dBi respectively.
Keywords: Antenna Array Uniform Array Binomial Array Dolph Chebyshev Array Genetic Algorithm Gain HPBW Max SLL Number of SLL And Radiation Pattern